2020
DOI: 10.1038/s41598-020-60903-9
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate response element binding protein (ChREBP) correlates with colon cancer progression and contributes to cell proliferation

Abstract: cancers are characterized by reprogrammed glucose metabolisms to fuel cell growth and proliferation. carbohydrate response element binding protein (chReBp) is a glucose-mediated transcription factor that strongly regulates glycolytic and lipogenic pathways. it has been shown to associate with metabolic diseases, such as obesity, diabetes and non-alcoholic fatty liver diseases. However, how it associates with cancers has not been well understood. In this study, ChREBP expression was assessed by immunohistochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…We observed a dose- and time-dependent component of ChREBPβ-mediated β-cell death in vivo, FACs-sorted human β-cells from T2D donors displayed a higher ChREBPβ:ChREBPα ratio than from non-diabetic donors, and increasing the ChREBPα abundance mitigated ChREBP-β-mediated cell death in vitro and in vitro in both rodent and human β-cells. These results are in concert with studies showing high levels of ChREBP correlate with poor diagnosis and increased rates of proliferation in certain forms of cancer 48 . Indeed, in many respects, ChREBPβ behaves very much like Myc in β-cells.…”
Section: Discussionsupporting
confidence: 83%
“…We observed a dose- and time-dependent component of ChREBPβ-mediated β-cell death in vivo, FACs-sorted human β-cells from T2D donors displayed a higher ChREBPβ:ChREBPα ratio than from non-diabetic donors, and increasing the ChREBPα abundance mitigated ChREBP-β-mediated cell death in vitro and in vitro in both rodent and human β-cells. These results are in concert with studies showing high levels of ChREBP correlate with poor diagnosis and increased rates of proliferation in certain forms of cancer 48 . Indeed, in many respects, ChREBPβ behaves very much like Myc in β-cells.…”
Section: Discussionsupporting
confidence: 83%
“…This upregulation is caused by gene amplification and DNA hypomethylation and occurs in concert with a cohort of neighboring genes on chromosome locus 20q [ 55 ]. Studies have shown that ChREBP mRNA and protein expression levels are significantly increased in colon cancer tissues compared to normal tissues [ 56 ]. Their expression positively correlated with colon malignancy and was suggested to contribute to cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…ChREBP knockdown by siRNA significantly inhibits aerobic glycolysis and the synthesis of lipids in colon cancer cells. Additionally, ChREBP knockdown activates p53, induces cell cycle arrest, and reduces colon cancer growth in vivo, indicating an oncogenic function for ChREBP [ 54 , 55 ]. Positive correlations of MLXIPL mRNA with glycolytic and lipogenic genes were also observed in a comprehensive chromatin immunoprecipitation analysis of human HCC and breast cancer.…”
Section: Transcription Factors Leading To Lipid Metabolism Rewiring In Cancermentioning
confidence: 99%